Ischemic Necrosis of the Gastric Remnant without Splenic Infarction Following Subtotal Gastrectomy - Park, Hwan Hee (Clin Endosc, 2018)
Gastric remnant necrosis after a subtotal gastrectomy is an extremely uncommon complication due to the rich vascular supply of the stomach. Despite its rareness, it must be carefully addressed considering the significant mortality rate associated with this condition. Patients vulnerable to ischemic vascular disease in particular need closer attention and should be treated more cautiously. When gastric remnant necrosis is suspected, an urgent endoscopic examination must be performed. We report a case of gastric remnant necrosis following a subtotal gastrectomy and discuss possible risk factors associated with this complication.